Obtenção e estudo de um compósito de matriz de poliéster e carga de resíduos de mármore - Costa, Larissa Caroline Fernandes (2017)
It presents a composite formed by polyester resin and load of marble dust residues (RPM) produced by the cut of ornamental stones. The residue produced was processed to obtain powders. Several composite formulations were tested by varying the load percentage relative to polyester, crystal or dark renin. All formulations chosen, 50% RPM, 100% RPM, 150% RPM, 200% RPM and 250% RPM presented feasibility of processing and obtaining the composite. The marble powder and composites produced were characterized for the determination of physical, mechanical and thermal properties. The results of the characterization of the composite formulations showed that the marble powder was present in the composite as a filler. The property in which the composite presented better results than the matrix resin was the impact strength. Analyzing the processability all the formulations of the composite were feasible, for the two resins studied. The composite has proven to be feasible for the manufacture of tables, chairs, planks, works of art, parts for bathrooms, partitions for environments, structures that do not require resistance to great efforts. An important advantage of the composite studied is the decrease in the amount of resin to be used, since the residue powder load can reach 250% in relation to the matrix, reducing the cost of the material obtained for the manufacture of various structures. The polymer composite proved to be feasible to replace natural marble and granite stones.